2022
DOI: 10.1029/2022jf006721
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Transport Modeling Based on Geological Data for Holocene Coastal Evolution: Wave Source Estimation of Sandy Layers on the Coast of Hidaka, Hokkaido, Japan

Abstract: Tsunami deposits are some of the few physical evidence that can be used to estimate the magnitude of earthquakes in the prehistorical period. As the historic records in Hokkaido are limited to ∼200 years, it is important to reconstruct paleoearthquakes using tsunami deposits. To estimate the rupture zone of paleoearthquakes based on tsunami deposits, conducting surveys at multiple sites and assuming a tsunami based on which the correlated tsunami deposits at each site are comprehensively reconstructed are nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Nakanishi and Ashi [ 25 ] previously developed models to understand sediment transport driven by tsunamis and typhoons in Shizunai, located along the central Hidaka coast. While Hokkaido is not frequently affected by large typhoons due to its location far from the equator, the estimated sand distribution around the river mouth, even under the impact of the most significant typhoon ever recorded in Hokkaido, reached altitudes of up to 1 m asl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakanishi and Ashi [ 25 ] previously developed models to understand sediment transport driven by tsunamis and typhoons in Shizunai, located along the central Hidaka coast. While Hokkaido is not frequently affected by large typhoons due to its location far from the equator, the estimated sand distribution around the river mouth, even under the impact of the most significant typhoon ever recorded in Hokkaido, reached altitudes of up to 1 m asl.…”
Section: Discussionmentioning
confidence: 99%
“…Radiocarbon dating of these tsunami deposits has indicated that most of these sand layers can correlate with tsunami deposits found in eastern Hokkaido. The wave source for the 17th-century tsunami deposits in Shizunai, central Hidaka, was estimated through sediment transport modeling, revealing that only the Mw 8.8 model within the Kuril Trench could accurately replicate the distribution of the sand layer [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since this discrepancy varies depending not only on the hydraulic conditions but also on the bottom sediment, past tsunamis require calculating sediment transport. Sediment transport modeling (STM) considering multiple grain sizes allows comparison of observed tsunami deposits on sedimentary structures and grain size composition as well as thickness distribution (Nakanishi and Ashi 2022). Therefore, STM can provide new constraints in estimating wave sources, even for multiple event layers with similar sediment distribution or inundation extent.…”
Section: Introductionmentioning
confidence: 99%
“…Along with hydraulic data, information on deposit thickness and erosion depth can be obtained from tsunami sediment transport simulations and the results of the simulations can be compared directly with the sedimentary data of tsunami deposits. As the application of tsunami sediment transport simulations in tsunami deposit research is still at its nascent stage, examples of paleotsunami source modeling using sediment transport simulations are scarce (Sugawara et al 2019;Dourado et al 2021;Nakanishi and Ashi 2022). Thus, the validity and limitations of the application of tsunami sediment transport simulations in tsunami source modeling have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Their deposit-based source modeling well reproduced the moment magnitude of the earthquake; however, the maximum slip was underestimated. Nevertheless, rectangular fault models are still dominantly used in source estimation of both modern and paleotsunamis (Satake et al 2013;Yamazaki et al 2018;Sugawara et al 2019;Dourado et al 2021;Nakanishi and Ashi 2022). Thus, an examination of the framework using the rectangular fault model can be useful to compare the results with those of the rectangular model reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%